Digital privacy awareness among selected millennials in Kuala Lumpur and Selangor / Raja Nur Syafiqah Raja Nazarruddin - Raja Nazarruddin, Raja Nur Syafiqah (Faculty of Business and Management, 2019)
Digital privacy is now a large part of concern in digital age. In recent years, the amount of cases of data breach had been increasing in a worrying number. One of the reasons is that the interest of scammers and hackers in obtaining private information. Thus, people need to know what are the factors that could influence their digital privacy awareness so that they can equipt themselves with necessary actions. The purpose of this study is to investigate the factors influencing digital privacy awareness among selected millennials in Kuala Lumpur and Selangor. There are four independent variables used which are vulnerability to privacy risk, perceived benefit, legal and government practices and protection behaviour meanwhile the dependent variable is digital privacy awareness. The method used to conduct this study is by distributing questionnaires to total of 400 respondents. Based on the results, the major factor that influences digital privacy awareness is protection behaviour and all of the variables are significant except perceived benefit.